Collaborative and Reflective Learning Approaches in Biology Teacher Preparation: Emerging Insights and Future Directions - Marlina, Reni; Yuenyong, Chokchai; Hamdani, Hamdani; Pamungkas, Rahmania; Zb, Aminah (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This study aims to analyze research trends and characteristics related to collaborative reflective learning in educational contexts, particularly among pre-service biology teachers, and to recommend courses that align with this strategy. The method used in this study was a Systematic Literature Review (SLR). The researchers reviewed 33 scientific articles selected based on the criteria of being in English, published in reputable journals indexed by Scopus, and published between 2000 and 2025. The results revealed a significant increase in publications on this topic since 2018, with a peak in 2020 and 2024, which may have been influenced by the COVID-19 pandemic and the application of technology in online learning. The results also revealed that the concept of